Enhancing students’ Learning Experiences Outside School (LEOS) using digital technologies - Coll, Sandhya Devi (Curtin University, 2015)
This thesis reports on an inquiry on enhancing students’ learning experiences outside school (LEOS) using digital technologies. The inquiry took the nature of an ethnographic case study which was conducted over a year. The case study involved a private religious school in rural New Zealand, where Year 10 (14 year old) students visited informal science institutions (ISIs) at the end of each school year. The sample comprised 65 students and 10 teachers. Two research questions guided this inquiry. The first research question sought to understand current practices involved in preparing and assessing students’ learning experiences at an ISI, in this case a predator-free native forest. Student, teacher, and ISI staff perceptions of these experiences were explored using semi-structured interviews, before, during, and after the visit. These data were triangulated using photographs, field-notes, unobtrusive classroom observations, student work-books, and teacher planning diaries. The findings from this first part of the study revealed that very little preparation was done for each LEOS and that the site visit was scheduled on the second last day of the school year. Additionally, the teachers who taught these topics were not necessarily involved in planning the visit and most did not accompany the students to the ISI. It appeared then that LEOS was seen as a reward instead of an informal learning experience where students could construct knowledge through social interactions. These findings then led to the second research question which explored an integrated learning model to enhance science learning when students and teachers engaged in LEOS.The second research question examined whether or not an intervention based on learning support provided by digital means had any effect on the desired learning outcomes when evaluated against the New Zealand Curriculum achievement standards. The same cohort of students now in Year 11 (15 years old) and their teachers were involved in the intervention part of the inquiry. This stage of the inquiry comprised a three phase intervention. The first phase of the intervention placed emphasis on improved pre- and post-visit planning for a Physics achievement standard titled AS90943, The Design Game-Keeping Your Home Warm. The ISI visited was the Show Home which provided the context for informal learning on vi building design and heat insulation. Students, teachers, and the ISI staffs’ perceptions of these experiences were explored using semi-structured interviews, before, during and after the visit. These data were triangulated using photographs, field-notes, making unobtrusive classroom observations, analysing student work-books, assessment results, and teachers’ planning diaries. The findings revealed a substantial improvement in both students’ engagement with the topic, their engagement with the ISI staff, and better performance in their summative assessment. While the teachers spent time to improve pre- and post-visit planning, this phase did not see the use of any social software technologies, even though the students were keen to share their findings with each other, digitally. The second phase of the intervention employed one tool of the learning management system, Moodle namely, forum. The achievement standard explored was Biology, AS90926, Report on Biological Issues.The ISIs visited were a pine forest (Rakau Paina Stand) beside the school, which involved experts on pest control from the Regional Council, and an Island Ecological Reserve, a predator-free forest (the same sight used for the first part of the study to address research question one). The concepts covered were biosecurity and biodiversity. The School Career Advisor accompanied the students who looked for volunteer job opportunities during school holidays. The teaching and learning utilised a blended learning environment where students and teachers collaborated using forum. Once again students, teachers, and the ISI staffs’ perceptions of these experiences were explored using semi-structured interviews before, during and after the visit. Data triangulation involved photographs, field-notes, unobtrusive classroom observations, student work-books, forum postings, assessment results, and teachers’ planning diaries. The summative assessment results revealed a slight improvement in student performance compared to the previous year. While students collaborated using forum, this phase did not see the use of wiki, which led to the third phase of the intervention. The third phase of the intervention integrated the second tool of Moodle called wiki. The achievement standard explored was on Space Science, AS90954, Lunar-Our Moon. The ISI visited was an Observatory. Student attainment on this standard showed a poor pass rate in previous years, attributed by the teachers to the lack of teaching resources. For this phase of the study, the concepts on astronomical cycles. affecting Earth were delivered using a blended learning approach. Data triangulation involved photographs, field-notes, and unobtrusive classroom observations, student work-books, wiki postings, assessment results, and teachers’ planning diaries.This phase saw improvement in pre- and post-visit planning, and co-construction of knowledge using wiki, which resulted in a substantial improvement in student attainment for this achievement standard. The findings from this inquiry suggest that science students can benefit from the use of an integrated learning model when engaging in LEOS. The New Zealand curriculum emphasizes contextualizing science learning, which it seems can be achieved by sound pre- and post-visit planning, and helping students collaborate and co-construct knowledge using digital technologies within learning management systems such as forum and wiki on Moodle. The findings of the third phase of this inquiry also have implications for including informal science education settings (ISIs) in the learning of science and potentially in science teacher preparation resulting in the development of positive attitudes (e.g., value, interest, excitement for science), an open mind for change, and confidence in teaching. It is also thought to help in the development of preservice teachers’ science skills as they themselves experience teaching in diverse contexts relating to the diverse needs of students. Another benefit for preservice teachers would be autonomy in learning because using ISIs to engage students with science learning provides for a deeper understanding of learning, along with diversifying their teaching strategies.